The visual system in eyelid myoclonia with absences. Issue 3 (11th August 2014) - Vaudano, Anna Elisabetta; Ruggieri, Andrea; Tondelli, Manuela; Avanzini, Pietro; Benuzzi, Francesca; Gessaroli, Giuliana; Cantalupo, Gaetano; Mastrangelo, Massimo; Vignoli, Aglaia; Bonaventura, Carlo Di; Canevini, Maria Paola; Bernardina, Bernardo Dalla; et al.
<x xml:space="preserve">Abstract</x> Objective To investigate the functional and structural brain correlates of eyelid myoclonus and absence seizures triggered by eye closure (eye closure sensitivity [ECS]). Methods Fifteen patients with eyelid myoclonus with absences (EMA, Jeavons syndrome), 14 patients with idiopathic generalized epilepsies (IGE) without ECS, and 16 healthy controls (HC) underwent an electroencephalography (EEG)‐correlated functional magnetic resonance imaging (fMRI) and voxel brain morphometry (VBM) protocol. The functional study consisted of 30‐second epochs of eyes‐open and eyes‐closed conditions. The following EEG events were marked and the relative fMRI maps obtained: (1) eye closure times, (2) spontaneous blinking, and (3) spontaneous and eye closure–triggered spike and wave discharges (SWD; for EMA and IGE). Within‐group and between‐groups comparisons were performed for fMRI and VBM data as appropriate. Results In EMA compared to HC and IGE we found: (1) higher blood oxygenation level–dependent (BOLD) signal related to the eye closure over the visual cortex, the posterior thalamus, and the network implicated in the motor control of eye closure, saccades, and eye pursuit movements; and (2) increments in the gray matter concentration at the visual cortex and thalamic pulvinar, whereas decrements were observed at the bilateral frontal eye field area. No BOLD differences were detected when comparing SWD in EMA and IGE. Interpretation Results demonstrated altered anatomo‐functional properties of the visual system in EMA. These abnormalities involve a circuit encompassing the occipital cortex and the cortical/subcortical systems physiologically involved in the motor control of eye closure and eye movements. Our work supports EMA as an epileptic condition with distinctive features and provides a contribution to its classification among epileptic syndromes. Ann Neurol 2014;76:412–427